2008
DOI: 10.1111/j.1743-6109.2008.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Testosterone Levels Are Associated with Ejaculatory Dysfunction

Abstract: Introduction The role of testosterone (T) in pathogenesis of ejaculatory symptoms has not been completely clarified. Aim To evaluate the possible contribution of T and hypogonadism in the control of the ejaculatory reflex, comparing subjects with premature ejaculation (PE) or delayed ejaculation (DE) to those without ejaculatory dysfunction. Methods A consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 49 publications
6
133
2
2
Order By: Relevance
“…13 Keleta et al 14 showed that the chronic treatment with T in rats significantly decreased serotonin (5-hydroxytryptamine (5-HT)) in brain. Serotonin is the most important central monoamine neurotransmitter that is involved in delaying ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Keleta et al 14 showed that the chronic treatment with T in rats significantly decreased serotonin (5-hydroxytryptamine (5-HT)) in brain. Serotonin is the most important central monoamine neurotransmitter that is involved in delaying ejaculation.…”
Section: Discussionmentioning
confidence: 99%
“…Few investigators have reported on the prevalence of DE. 17,23,37,41,58 Rates for this disorder vary from 1% to 10%. It is speculated that the prevalence of DE or anejaculation in elderly men, many of whom are no longer sexually active, could be much higher.…”
Section: Ejaculation Dysfunctionsmentioning
confidence: 98%
“…1 Prevalence estimates of PE vary widely between studies, with reports ranging from around 3% 2 to around 30% 3 depending on definition and diagnostic criteria. For its etiology, psychological, environmental and contextual factors are all still being considered, 4,5 whereas recent research has focused on neurobiological, 6 endocrine 7,8 and genetic explanatory frameworks. 9,10 In recent years, researchers have tended to favor theoretical approaches that incorporate several different etiological factors to PE.…”
Section: Introductionmentioning
confidence: 99%